1996
DOI: 10.2307/3870419
|View full text |Cite
|
Sign up to set email alerts
|

A Polyketide Synthase Is Required for Fungal Virulence and Production of the Polyketide T-Toxin

Abstract: Race T of the fungal pathogen Cochliobolus heterostrophus is highly virulent toward Texas male sterile (T) maize and differs from its relative, race O, at a locus (Tox1) that is responsible for the production of T-toxin, a family of linear long-chain (C35 to E41) polyketides. In a previous study, the restriction enzyme-mediated integration procedure was used to mutagenize and tag Tox1. Here, we report that the DNA recovered from the insertion site of one mutant encodes a 7.6-kb open reading frame (2530 amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 22 publications
1
66
0
1
Order By: Relevance
“…In this study, we identified two NRPS candidates ( Table 2 ). PKSs are also associated with the biosynthesis of toxins in Cochliobolus heterostrophus, Cercospora nicotianae, Botrytis Cinerea , and Gibberella fujikuroi (Yang et al, 1998; Proctor et al, 1999; Choquer et al, 2005; Dalmais et al, 2011). In this study, the expression of two PKS genes only in the susceptible host environment may contribute to the proliferation of C. austroafricana .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified two NRPS candidates ( Table 2 ). PKSs are also associated with the biosynthesis of toxins in Cochliobolus heterostrophus, Cercospora nicotianae, Botrytis Cinerea , and Gibberella fujikuroi (Yang et al, 1998; Proctor et al, 1999; Choquer et al, 2005; Dalmais et al, 2011). In this study, the expression of two PKS genes only in the susceptible host environment may contribute to the proliferation of C. austroafricana .…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of PKS genes and PKs found in Pezizomycotina led to speculation, including our own (6,43), that HGT is involved in generating and maintaining this diversity (ref. 44 and references therein).…”
Section: Diversification Of Pks Genes Among Species In the Pezizomycomentioning
confidence: 99%
“…To address these questions, we performed phylogenetic analyses on the amino acid sequences of KS domains encoded by all previously characterized fungal PKS genes and by all putative PKS genes extracted from genomic sequences of five taxonomically diverse fungal species in the Ascomycota, subphylum Pezizomycotina (4) [the saprobe Neurospora crassa (5); the maize pathogens Cochliobolus heterostrophus (Bipolaris maydis) (6,7) and Gibberella moniliformis (Fusarium verticillioides) (8); the cereal pathogen Gibberella zeae (Fusarium graminearum) (8); and the cosmopolitan dicot pathogen Botryotinia fuckeliana (Botrytis cinerea) (8)]. We also searched for PKS genes in the genomes of three earlier diverging ascomycetes [Saccharomyces cerevisiae (9), the plant pest Eremothecium (Ashbya) gossypii (10), (both in the Saccharomycotina), and the yeast saprobe Schizosaccharomyces pombe (11) (Taphrinomycotina)].…”
mentioning
confidence: 99%
“…These genes are involved in the Penicillium freii IBT 3464 from the culture collection at the biosynthesis of mycotoxins such as 6-methylsalicylic acid Department of Biotechnology, Technical University of (Beck et al 1990 ;Fujii et al 1996), sterigmatocystin (Yu Denmark, Lyngby, was used throughout these studies. The and Leonard 1995), aflatoxin (Chang et al 1995 ;Feng and strain was grown on Czapek yeast autolysate agar or broth Leonard 1995), T-toxin (Yang et al 1996), and in the biosyn- (Pitt 1979). Xanthomegnin was detected by the TLC-agar thesis of a polyketide precursor to a green spore pigment plug method (Filtenborg et al 1983).…”
Section: Penicillium Freii Strains Culture Conditions Andmentioning
confidence: 99%